EMPLOYEE PAYROLL INFORMATION SYSTEM (CASE STUDY: PT SURYAMEGA JAYA STEEL) - Panjaitan, Herlina; Afni, Nurul; Sumarno, Heny; Maulana, Yana Iqbal; Komarudin, Rachman (Journal of Information System, Informatics and Computing, 2023)
The payroll system is a series of business activities that aim to complete all payments for services that have been made by employees. Payroll is a process within an organization/agency that is prone to problems. Data processing that is still done manually can result in slow preparation of salary reports which results in delays in payment of salaries to employees plus if there is an error in calculating the salary it becomes inaccurate. In this study, the author tries to design a web-based payroll system at PT Suryamega Jaya Steel, which until now has not been computerized. This web-based system was written to simplify the payroll transaction process so that salary calculations are more accurate and employees can print payslips. The author designed a web-based payroll information system using the PHP programming language. The method used in designing the software for this payroll application is in the form of the waterfall method, data collection techniques, observation, and interviews. The design of this information system is the best solution to solve the problems that exist in this company. A computerized system is better than a manual system because a computerized system can run more safely than the system used before.